A Comparison of DSM-IV-TR and DSM-5 Diagnostic Criteria for Gambling Disorder in a Large Clinical Sample - Jiménez-Murcia, Susana; Granero, Roser; Fernández-Aranda, Fernando; Sauvaget, Anne; Fransson, Andreas; Hakansson, Anders; Mestre-Bach, Gemma; Steward, Trevor; Stinchfield, Randy; Moragas, Laura; Aymamí, Neus; Gómez-Peña, Mónica; et al. (Frontiers in Psychology, 2019)
Background and aims: Gambling-related crimes are known to be associated with gambling disorder (GD). Due to a lack of consensus in the scientific community regarding the relevance of this diagnostic criterion, it was removed from the DSM-5. The primary aim of this study was to investigate through structural equation modeling (SEM) whether higher GD severity in treatment-seeking GD patients with a criminal record is mediated through the illegal acts criterion itself, or whether it can be better explained by other related clinical factors. Methods: An initial sample of 2,081 patients seeking treatment for gambling problems was included in the sample. SEM was used to evaluate the mediational role of the illegal acts criterion between the sex, age and personality traits, gambling severity, and comorbid depression levels. Comparisons between patients with coinciding and divergent DSM criterion for GD diagnosis were carried out. Results: Illegal acts mediated the relationship between personality traits and GD severity: younger age, high levels of novelty seeking, and low levels of self-transcendence increased the risk of endorsing the illegal acts criterion. No differences between coincident-divergent groups in terms of DSM-IV and DSM-5 diagnosis were found with regards to sex (p=.878), education level (p=.387) or civil status (p=.792). Discussion and conclusions: The results obtained in the present study offer new insights into the utility of using a history of illegal acts, their different personality characteristics and psychopathology to categorize GD patients. Our findings suggest that patients who engage in criminal behavior may require a more comprehensive intervention.